(untitled) (Journal of Partial Differential Equations, 2020)
In the present paper, we study the long time behaviour of solutions for the long-short wave equations with zero order dissipation. We first construct the global weak attractor for this system in H²_per × H¹_per. And then by exact analysis of two energy equations, we show that the global weak at attractor is actually the global strong attractor in H²_per.